EVALUASI KINERJA GURU DI SEKOLAH MENENGAH PERTAMA NEGERI 7 BATANGHARI PROVINSI JAMBI - Abdullah Yunus; Madyan Madyan; Wahyu Hidayat; Muhamad Sa'id; Ninda Dwi Lestari; M. Rizki Alfian (Jurnal Manajemen Pendidikan, 2026)
This research aims to present teachers at SMPN 7 Batanghari, Jambi Province, with a focus on planning, implementation and obstacles faced in the evaluation process. Qualitative methods are used to explore teachers' experiences, perspectives and motivations through interviews, observations and document analysis. The research results show that teacher performance evaluations are carried out regularly every semester, with the aim of improving teacher performance and professionalism. Even though there is a complete evaluation system and the implementation of the Independent Curriculum which provides uniqueness in learning, there are still obstacles such as limited time, lack of teacher commitment, and difficulties in implementing a culture of discipline. This research emphasizes the importance of effective communication and school management support to overcome these challenges, so that the quality of education at SMPN 7 Batangharican continue to be improved.